Esensi Wali Nikah Perspektif Al-Qur’an Surat An-Nisa dan Relevansinya pada Kehidupan Masyarakat Modern - Agus Fiatna (Syntax Idea)
This article discusses the essence of marriage guardians based on the perspective of the Al-Qur'an Surah An-Nisa in the context of modern society. The aim of this research is to provide an in-depth analysis of the essence of marriage guardians and their relevance in dealing with the complexity of modern society. The research method used is analysis of the Al-Qur'an text with an interpretive approach. The research results show that the essence of marriage guardians emphasized in Surah An-Nisa has strong and binding relevance from the past until now, even though it requires adjustments to applicable social and legal norms. An-Nisa's letter emphasized that marriage guardians have the main duties and functions as well as responsibilities to protect women's rights in marriage, so that the essence of marriage guardians in Islamic law is that a marriage is not valid without a marriage guardian, either nazab guardian or judge guardian.